Achieving corporate sustainability performance: The influence of corporate ethical value, and leader-member exchange on employee behaviors and organizational performance - Stacy H. Lee (Fashion and Textiles, 2020)
Abstract This study investigated how corporate sustainability performance can be attained through the interface of corporate ethical values and leader-member exchange, and how employees’ positive and negative behaviors can influence these relationships. A total of 310 data sets were collected and used to test our hypotheses. To assess the factorability of the variables, exploratory factor analysis was conducted, and confirmatory factor analysis was conducted to test the fit and validity of the measurement model. Then, the structural model proceeded to test the hypotheses. The results of this study found that employee behaviors can highly influence corporate sustainability performance. Depending on contextual or/and relational factors, employee behaviors can either encourage more organizational citizenship behavior or alleviate counterproductive work behavior. These findings demonstrate that it is critical not only to create an ethical working environment but also to develop quality relationships with direct managers.